Symbols of Integrity: A Semiotic Study of "Transparency, Accountability, Justice, and Fairness" in Government Discourse - Dennis B. Anduyan (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Governments say a great deal about themselves before a single policy is implemented — through seals, portals, posted budgets, and program names that promise transparency, accountability, justice, and fairness. This qualitative study asked what those promises are actually built from. Using semiotic analysis, it examined the signs Davao de Oro's provincial government uses on its official online portal to convey the four values, then asked what those signs imply about governance legitimacy once matched against the wider empirical record. Transparency surfaced most often in the business and investment climate, trade and commerce, public participation, information and communication technology, climate adaptation, fiscal budget disclosure, the policy and regulatory framework, and disaster risk communication. Accountability was carried mainly by education and skills reporting, fiscal and revenue management, audit and infrastructure disclosure, watershed and forest stewardship, solid waste control, and inter-agency collaboration. Justice appeared through peace-and-order messaging, rural electrification, livelihood generation, skills certification, and land-use compliance. Fairness was expressed through social welfare services, disaster risk reduction, agriculture and fisheries support, health access, housing, and water and sanitation programming. Reading these symbols against the broader literature produced two organizing dimensions: Structural Integrity, concerning how governance is worded and represented, and Performative Legitimacy, concerning whether the symbol is actually enacted. The two do not always move together, and where they diverge, the study argues, is where public trust is most at risk.